Vue d'ensemble de la végétation des îles Baléares - de Bolòs, O; Molinier, R (Vegetatio, 1969)
The vegetation of the Balearic Islands is pure mediterranean. The climax forests belong to the northern mediterranean alliance of the Quercion ilicis (rainy regions in Majorca and Menorca) and to the southern mediterranean community of the Oleo-Ceratonion (Querco-Lentiscetum with Iberic affinity in Ibiza; community with Ceratonia siliqua and Cneorum tricoccum in the dry region in Majorca, community with Otea europaea and Prasium majus in the driest region in Menorca). Communities rich in endemic plants characterize the karst of the high summits in Majorca, and coastrocks of the windy shores in Majorca and Menorca. The tyrrhenic influence, important in the Gymnesies (Majorca and Menorca), is more feeble in the group of the Pithyuses (Ibiza and Formentera), nearer to the Iberic Peninsula.
Keywords: groupements vegetaux; Iles Baleares; Maquis (voyant)